REALISASI DEMOKRASI DAN KONSTITUSI DALAM UPAYA PENGUATAN MAHKAMAH KONSTITUSI DI INDONESIA (Solusi, 2023)
The purpose of this study is to find out the extent of the role of the Constitutional Court in Indonesia's constitutional life when it is associated with the idea of constitutional democracy and legal state democracy. The method used in this study is normative legal research that focuses on positive legal norms. The Constitutional Court in Indonesia's constitutional system still needs to be given a record of improvement, especially regarding the ethical behavior of constitutional judges who often give information to the press about cases that will, are, or have been handled. It can often be witnessed, for example, that the Chief Justice commented on the rulings he had made. Supposedly, constitutional judges, let alone the Chief Justice, should be able to "live in silence" and place their verdicts as their representatives. Thus, there is no need for the Chief Justice to give additional information, clarification, or whatever his name may be, on the judgment he has made. Nevertheless, in general, the Constitutional Court has succeeded in carrying out the mandate of the constitution.